The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.5271/sjweh.2409
|View full text |Cite
|
Sign up to set email alerts
|

Biological monitoring of occupational exposure to tetrachloroethene.

Abstract: Biological monitoring of occupational exposure to tetrachloroethene. Scand j work environ health 9 (1983) 273-281. In the breathing zone of 32 workers concentrations of tetrachloroethene were measured during five consecutive workdays. The feasibility of biological monitoring was tested by the measurement of the concentrations of tetrachloroethene in blood and exhaled air and the urinary excretion of trichloroacetic acid and trichloroethanol. The best parameter to estimate the time-weighted average exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…2,3,10 Exposure of children could occur through inhalation of solvents used at home or brought home from the workplace on the parents' breath. 19 Previous epidemiologic studies have found positive associations between childhood leukemia and painting on the job during the prenatal 7,10,20 and postnatal 10 periods. Each of the activities associated with an elevated risk of childhoodALL involves exposure to organic solvents, some of which are known or possible human carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,10 Exposure of children could occur through inhalation of solvents used at home or brought home from the workplace on the parents' breath. 19 Previous epidemiologic studies have found positive associations between childhood leukemia and painting on the job during the prenatal 7,10,20 and postnatal 10 periods. Each of the activities associated with an elevated risk of childhoodALL involves exposure to organic solvents, some of which are known or possible human carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…The low cost and simplicity of the breath sampling (end-exhaled air) method enabled expired air samples to be collected in virtually all participating workers. Breath (end-exhaled air) analysis has the great advantage of being noninvasive 14,15) . The results of this study showed that some workers in dry-cleaning shops were highly exposed to perchloroethylene; therefore control measures should be done for decreasing the airborne perchloroethylene level.…”
Section: Discussionmentioning
confidence: 99%
“…The nitrogen carrier gas flow-rate was 30 ml/min. For end-exhaled air samples of the same participants, individuals were asked to exhale normally into a 1 liter Tedlar TM air bags (SKC, eighty four PA) until it was filled [11][12][13][14][15] . All the samples from end-exhaled air samples were analyzed for perchloroethylene using the same Philips Unicam PU 4410 gas chromatograph equipped with the same column and detector.…”
Section: Methodsmentioning
confidence: 99%
“…Residing near dry-cleaning facilities or storing recently dry-cleaned clothes at home can contribute to increased blood tetrachloroethene levels (Begerow et al, 1996;Popp et al, 1992). In contrast, tetrachloroethene blood levels in occupationally exposed workers have been reported to be many thousand times higher than the unexposed general population (Begerow et al, 1996;Furuki et al, 2000;Monster et al, 1983). The occupational biological exposure index associated with an 8-hour exposure of 25 ppm is 500 μg/L tetrachloroethene in blood (ACGIH, 2007).…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%